Human in vitro assay for irreversible electroporation cardiac ablation - Casciola, Maura; Feaster, Tromondae K.; Caiola, Michael J.; Keck, Devin; Blinova, Ksenia (Frontiers in Physiology, 2023)
Pulsed electric field (PEF) cardiac ablation has been recently proposed as a technique to treat drug resistant atrial fibrillation by inducing cell death through irreversible electroporation (IRE). Improper PEF dosing can result in thermal damage or reversible electroporation. The lack of comprehensive and systematic studies to select PEF parameters for safe and effective IRE cardiac treatments hinders device development and regulatory decision-making. Human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) have been proposed as an alternative to animal models in the evaluation of cardiac electrophysiology safety. We developed a novel high-throughput in vitro assay to quantify the electric field threshold (EFT) for electroporation (acute effect) and cell death (long-term effect) in hiPSC-CMs. Monolayers of hiPSC-CMs were cultured in high-throughput format and exposed to clinically relevant biphasic PEF treatments. Electroporation and cell death areas were identified using fluorescent probes and confocal microscopy; electroporation and cell death EFTs were quantified by comparison of fluorescent images with electric field numerical simulations. Study results confirmed that PEF induces electroporation and cell death in hiPSC-CMs, dependent on the number of pulses and the amplitude, duration, and repetition frequency. In addition, PEF-induced temperature increase, absorbed dose, and total treatment time for each PEF parameter combination are reported. Upon verification of the translatability of the in vitro results presented here to in vivo models, this novel hiPSC-CM-based assay could be used as an alternative to animal or human studies and can assist in early nonclinical device development, as well as inform regulatory decision-making for cardiac ablation medical devices.